Brand Loyalty: Strengthening Brand Experience and Brand Satisfaction - Grace Yuwono; Dudi Anandya (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
This study aims to examine the effect of brand experience on Consumer-Based Brand Equity, satisfaction and loyalty at Starbucks in Surabaya. This research was conducted using SEM and processed using SPSS and AMOS. The number of respondents used is 210 respondents who live in the city of Surabaya and have purchased and enjoyed dine-in facilities and services. The results showed that brand experience had a positive effect on brand awareness, identification, physical quality, staff behavior, ideal self-congruence and lifestyle congruence. Brand awareness, identification, physical quality, staff behavior, ideal self-congruence have a positive effect on brand satisfaction. Brand satisfaction has a positive effect on brand loyalty. However, lifestyle congruence has no effect on brand satisfaction.